Education marginalization in sub-Saharan Africa policies, politics, and marginality - Mfum-Mensah, Obed, 1965- (Lexington Books, 2018)
"This book focuses on education policy framework for educating marginalized children in sub-Saharan Africa. It uses "marginality" as a critical discourse to highlight the complicated ways education policy making in sub-Saharan Africa have constructed and perpetuated marginality in the region since Africa's encounters with Europe. The book is organized around two parts, each of which discusses a specific dimension of the marginality and education policy nexus. Part I focuses on theorizations of marginality and education. The theoretical framework on marginality and education outlines the definitional and conceptual backgrounds on marginality - the complicated ways policies of the Christian missionaries, colonial governments and postcolonial governments constructed and perpetuated marginality in the region. Part II focuses on addressing the issue of marginality from theory to practice. These chapters highlight the ways policies shaped the educational development, schooling processes, and educational outcomes of selected marginalized communities and groups. Attention is given to schooling in rural communities, the complexities of girls' education in rural contexts, education of Zongo Muslim communities, violence in school in rural contexts, and education collaboration in rural traditional communities. The book argues that education policies in sub-Saharan Africa fail to address the educational needs of marginalized children because current policy frameworks ae not based on examination of colonial policies which created the existing marginality. In order to implement policies that address policy gaps and meet the educational needs of marginalized children, strong synergies are necessary between education policy makers, other education stakeholders, and marginalized communities."--